The epidemiology of cardiac surgery-associated acute kidney injury - Hoste, E A; Cruz, D N; Davenport, A; Mehta, R L; Piccinni, P; Tetta, C; Viscovo, G; Ronco, C (International journal of artificial organs, 2008)
To describe current knowledge on the epidemiology of cardiac surgery-associated acute kidney injury (CSA-AKI) and to formulate recommendations for clinical practice and a research agenda. After a modified Delphi analysis by the Acute Dialysis Quality Initiative (ADQI), 4 questions on the epidemiology of CSA-AKI and recommendations for clinical practice and a research agenda were formulated and addressed. Existing studies on CSA-AKI use over 35 different definitions for CSA-AKI. In addition, there may be important differences in patient characteristics and procedures. This explains the significant variations in reported incidence. Most studies report on CSA-AKI as defined by the need for renal replacement therapy. However, even small decreases in kidney function are associated with a worsened outcome. The workgroup formulated the recommendation to use the AKIN consensus criteria for AKI. One should differentiate early CSA-AKI, caused by the procedure, and late CSA-AKI, associated with the procedure. There may be different clinical scenarios: acute on chronic CSA-AKI, AKI prior to CS, and AKI occurring post CS. Risk factors should be differentiated between pre-, intra-, and post-CS, and between patient-, process-, and procedure-related. Endpoints should include both short-term and long-term outcomes. Existing data on the epidemiology of CSA-AKI are difficult to compare due to variations in definition and patient cohort. A modified Delphi analysis resulted in a series of recommendations for future research on CSA-AKI.